2014
DOI: 10.1016/j.jprot.2014.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic signatures of the oyster metabolic response to herpesvirus OsHV-1 μVar infection

Abstract: This study is the first 2-DE proteomic analysis dedicated to the pathogenesis of ostreid herpesvirus 1 (OsHV-1 μVar) in oyster Crassostrea gigas, the most important bivalve produced in the world. OsHV-1 has affected oysters every year since 2008. All the proteins identified in this paper are key targets involved in OsHV-1 infection processes. We presented evidence that the metabolic changes during infection in oyster somehow resemble the Warburg effect occurring in cancer cells. This work constitutes a real ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 88 publications
1
47
0
1
Order By: Relevance
“…6) and 2 peroxiredoxin-like genes (Cg08877, p ¼ 0.0368 and Cg24227, p ¼ 0.048) (Table S4). A previous proteomic study also showed that a catalase and a glutathione S-transferase gene were down- regulated in OsHV-1mVar challenged oysters [70].…”
Section: Oxidative Burst and Destruction Of Viral Componentsmentioning
confidence: 81%
“…6) and 2 peroxiredoxin-like genes (Cg08877, p ¼ 0.0368 and Cg24227, p ¼ 0.048) (Table S4). A previous proteomic study also showed that a catalase and a glutathione S-transferase gene were down- regulated in OsHV-1mVar challenged oysters [70].…”
Section: Oxidative Burst and Destruction Of Viral Componentsmentioning
confidence: 81%
“…However, the question of how VDAC responds to pathogenic infection has not been widely studied. Some reports have shown the upregulation of VDAC in response to pathogen infection, such as oysters challenged by herpes virus OsHV-1 [56], flounder (Paralichthys olivaceus) infected by Scophthalmus maximus Rhabdovirus [57], and shrimp infected by white spot syndrome virus (WSSV) [58]. A further study on whether the upregulation of VDAC in shrimp was a cell defense mechanism or was induced by WSSV pathogenesis was performed by Wang et al [59], who found that when the expression of VDAC was silenced, infection was delayed, and the mRNA expression of VDAC was increased following WSSV infection in VDAC knocked-down shrimp.…”
Section: Immune-related Proteinsmentioning
confidence: 99%
“…It has long been an interesting question how the manila clam could be survived in response to the environmental stresses involved in the fluctuation of salinity. Many studies have been performed to reveal the alterations of mRNA expression 1720 and protein expression 2124 under abiotic and biotic stresses in the oyster 25 , while expression profiling of miRNAs under osmotic stress remains largely unexplored in clams.…”
Section: Introductionmentioning
confidence: 99%